Salinization Process on Sand Membrane as a Simulation of Sea Water Intrution and Tidal Flood Effect - Akfia Rizka Kumala; Budi Indra Setiawan; Satyanto K Saptomo; Rudi Yanto (Departemen Teknik Sipil dan Lingkungan, IPB University, 2016)
Salinization process through a membrane of sand is presented in this paper. Two treatments were performed here. Treatment 1, saline water flowed continuously from below the membrane with a stable unsaturated water content depicted as a simulation of sea water intrusion. Treatment 2, the membrane was inundated with saline water depicted as a simulation of flooding. Two kinds of membrane used which were black and white sand. Black sand had saturated water content (θs) 0.35 cm3/cm3, and the white sand 0.52 cm3/cm3. The highest to the lowest evaporation rate were flooded black sand, unflooded black sand, flooded white sand, and unflooded white sand membranes. Flooded and unflooded black sand membrane had higher temperature than flooded and unflooded white sand membrane. Most salt crystals were produced by the not flooded membrane amounted to 14.7 gram and 15 gram.Keywords : salinization, sand membrane, saline water, evaporation